Negotiation and “Influence” in the Arts: Exchanging Objects between France and Senegal in the 1960s - (:unkn) unknown (My University, 2022)
Based on unpublished archives, this paper examines the background, conditions, and modalities of an exchange of French tapestries for African objects, which took place in 1966–1967 between France and Senegal. It analyzes the role attributed to the objects by the two countries, their symbolic values, and the philosophical and political negotiations involved in this exchange, at a time of independence in Africa, Françafrique, and the Cold War. The aim is to understand why the medium and technique of the tapestry were chosen in light of the political and cultural agenda of the first Senegalese president, Léopold Sédar Senghor (1906–2001).
Keywords: African Research